Sister Cities Relations: Yesterday, Today and Tomorrow - Sllalahi, Robert P. (Forum Manajemen, 1998)
Sister City relations has been widely known abroad and the benefit of it has been felt in the context of bringing closer relationship among nations, even in materializing mutual beneficial cooperation among countries which conduct this partnership system.